An Application of Multi-Verse Optimizer for Optimal Reactive Power Dispatch Problem - M. H., Sulaiman; Zuriani, Mustaffa; Mohd Rusllim, Mohamed; Omar, Aliman (2016)
This paper proposes a new algorithm namely Multi-Verse Optimizer (MVO) in solving the Optimal Reactive Power Dispatch (ORPD) problem. It is inspired from the three main concepts in cosmology viz. white hole, black hole and wormhole. These concepts are developed mathematically to perform exploration, exploitation and local search respectively. This algorithm is applied to obtain the best combination of control variables such as generator voltages, tap changing transformer’s ratios, reactive compensation devices as well as real power generation.In this paper, to show the effectiveness of MVO into ORPD problem, IEEE-30 bus system with 25 control variables is utilized and compared with recent algorithms available in literature. The result of this study shows that MVO is able to achieve less power loss than those determined by other techniques.